A REVIEW OF LABORATORY TECHNIQUES FOR DETECTING LEPTOSPIROSIS - Jain, Monika; Nigam, R. K.; Malik, Reeni (International Journal of Current Pharmaceutical Research, 2015)
Occupational and recreational exposure to leptospirosis occurs in both the developed and developing countries. Timely laboratory confirmation of the disease is necessary to ensure a favourable clinical outcome and it is not possible to diagnose leptospirosis with certainty, on clinical grounds alone due to its inconsistent manifestations. Dark-field microscopy has multiple limitations. Many serological tests are easy to perform with minimum skills and laboratory facilities. To make a reliable diagnosis, it is essential to use multiple techniques together or in succession. Microscopic agglutination test is considered the gold standardâ€ but requires paired sera, maintenance of live cultures of leptospires and is not useful for guiding early clinical management. Though the Polymerase Chain Reaction requires special equipment and expertise, it is useful for diagnosing leptospirosis in the first week of illness. Culture provides definite proof of leptospiral infection and helps in identifying locally pathogenic serovars. However, it is not useful as a diagnostic tool because by the time diagnosis is made by culture, antibodies are already detectable by serological techniques. Sero-surveillance helps in identifying high-risk individuals, high-risk geographical areas, outbreaks, animal reservoirs, new serological variants and their geographical distribution. This review discusses various techniques for laboratory diagnosis of leptospirosis compared the technical limitations in terms of sensitivity, specificity and turnaround time. Based on the discussed facts, clinicians can decide the suitable technique of detections on case to case basis.